Connecting People to Their Governments. - Docksai, Rick (Futurist)
The article reports on the growing role of cell phones and other handheld devices for Internet access in empowering disadvantaged communities and enhancing democracy. Nicol Turner-Lee, vice president and director of the Media and Technology Institute at the Joint Center for Political and Economic Studies in the U.S., says cell phones present a lower barrier to entry to low-income minority or older people. She urges government agencies to make more information about their own operations Internet-accessible.